The edge of galaxy formation: I. formation and evolution of MW-satellite analogues before accretion - Macciò, Andrea V.; Frings, Jonas; Buck, Tobias; Penzo, Camilla (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. The satellites of the Milky Way and Andromeda represent the smallest galaxies we can observe in our Universe. In this series of papers, we aim to she
Gesehen am 13.07.2018